Holocaust Scholarship
XIII, 258 p.
Keywords: Leading international Holocaust scholars reflect upon their personal experiences and professional trajectories over many decades of immersion in the field. Changes are examined within the context of individual odysseys, including shifting cultural milieus and robust academic conflicts.